Antidepressant- and Anxiolytic-like Effects of Pomegranate: Is It Acting by Common or Well-Known Mechanisms of Action? - Erika Estrada-Camerena; Carolina López-Rubalcava; Nelly Maritza Vega-Rivera; María Eva González-Trujano (Plants, 2024)
The pharmacological effects of pomegranates have been described considering metabolic aspects such as hypoglycemic and hypolipidemic activities. The pomegranate extract has activity on the central nervous system (CNS) as a natural antidepressant and anxiolytic. The chemical composition of pomegranates is complex since the bioactive compounds are multiple secondary metabolites that have been identified in the extracts derived from the peel, seed, flowers, leaves, or in their combination; so, it has not been easy to identify an individual compound as responsible for its observed pharmacological properties. From this point of view, the present review analyzes the effects of crude extracts or fractions of pomegranates and their possible mechanisms of action concerning antidepressant- and anxiolytic-like effects in animal models. Serotonin receptors, estrogen receptors, the peroxisome proliferator-activated receptor gamma (PPARγ), or monoamine oxidase enzymes, as well as potent antioxidant and neuroplasticity properties, have been described as possible mediators involved in the antidepressant- and anxiolytic-like behaviors after pomegranate treatment. The pharmacological effects observed on the CNS in experimental models associated with a specific stress level suggest that pomegranates could simultaneously modulate the stress response by activating several targets. For the present review, scientific evidence was gathered to integrate it and suggest a possible pathway for mediators to be involved in the mechanisms of action of the pomegranate’s antidepressant- and anxiolytic-like effects. Furthermore, the potential benefits are discussed on comorbid conditions with anxiety and depression, such as perimenopause transition and pain.